Study on Activity of Cocoa Ethanolic Extract against Shigella dysenteriae - Ariza Budi Tunjung-Sari; Enny Suswati; Diana Chusna Mufida; Alfa Rianul Setiawan Rianul Setiawan; Alvin Isnaini; Mochamad Rizal; Teguh Wahyudi; Misnawi Jati (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2016)
Shigella dysenteriae is a gastrointestinal pathogen which shows resistance to antibiotics. A study has been conducted to investigate alternative antibacterial agents, due to the emerging resistance of S. dysenteriae to ciprofloxacin and other antibiotic classes. In this study, antibacterial properties of cocoa ethanolic extract (CEE) and its impact on growth and morphology of S. dysenteriae were evaluated. The effect of CEE on bacterial growth was assayed by using agar-well diffusion method and by observing morphological changes of bacterial cells through the use of scanning electron microscopy (SEM). Furthermore, CEE was also applied orally to mice infected with S. dysenteriae. The intestinal fluids was cultured in selective medium to evaluate growth of S. dysenteriae colonies. This study demonstrated that CEE at concentrations of 15.6 mg/mL inhibited S. dysenteriae growth, and at concentrations of 500 mg/mL and 1,000 mg/mL exhibited equal activity to 6.5 g/mL of ciprofloxacin. SEM showed that S. dysenteriae cells had formed filaments, indicating that CEE caused cellular stress to S. dysenteriae. In in vivo assay, CEE showed suppression of S. dysenteriae colony in the mice intestine. This research suggests that CEE could potentially be used as antibacterial agent againsts S. dysenteriae.